Evaluating the Efficacy of the Zelisken Ball in Shortening the First Stage of Labor: A Quasi-Experimental Study - Mutaqin, Zeni Zaenal; Lidya , Nurul; Astuti, Isroni; Meilani , Niken (JURNAL INFO KESEHATAN, 2023)
During labor, mothers frequently report having excruciating contractions that continue for hours or even days. An assistive gadget is required to expedite labor and aid in the baby's head drop. The Zelisken Ball, an invention of the research group, is a bolster-shaped ball used in basic exercises or physical care. The study aimed to determine whether using the Zelisken Ball could shorten the time pregnant mothers spend in the first stage of labor. Pregnant women's level of comfort and satisfaction while using it, along with its effects on each delivery stage, were highlighted. Using a control group, the study used a quantitative methodology and a quasi-experimental post-test-only design. Purposive sampling was employed to identify 50 postpartum patients for the sample. The Zelisken Ball was utilized by the intervention group in this study, while the Peanut Ball was used by the control group. Questionnaires were used to gather data, and SPSS software was implemented to perform an Independent Sample t-test to determine differences between the two groups. The mothers who utilized the Zelisken Ball advanced through the first stage of labor more quickly, according to the data, with a difference of 1.29 hours (77.4 minutes) between them and the control group (8.3 hours) who used the Peanut Ball. The results of the data analysis indicate that mothers who used the Zelisken Ball and those who utilized the Peanut Ball had significantly different first-stage labor durations (p-value of 0.026, <0.05). As a result, the Zelisken Ball shows great promise as a useful tool for accelerating the early stage of labor. The research has been modified to create Zelisken, which is two-thirds the size of a peanut ball and has an indentation of ½ on the ball. The outer material of Zelisken is made of Oscar fabric, and the inside is filled with foam, whereas the peanut ball is made of PVC and has an interior filled with air. Future research, however, needs to increase the sample size to include a wider range of respondents to strengthen the findings' generalizability.